Regulation of Leukocyte-Endothelium Interaction by Fibrinogen - Altieri, Dario C. (Thrombosis and Haemostasis, 1999)
The binding of neutrophils and mononuclear cells to vascular endothelium is an essential prerequisite in maintaining effective immune-inflammatory responses. This process has been unraveled as a regulated “adhesion cascade” that involves the expression of multiple adhesion receptors of the integrin, selectin, and immunoglobulin gene superfamilies on both cell types. These adhesive interactions are modulated by disparate environmental signals, ranging from inflammatory and chemotactic cytokines to changes in shear force at the vessel wall. Although of paramount importance in the preservation of immune-inflammatory surveillance, dysregulation of leukocyte-endothelium interaction also constitutes one of the earliest molecular events in the pathogenesis of such vascular diseases as atherosclerosis. This dysregulation leads to the aberrant accumulation of mononuclear cells in the damaged intima.Recently, the interaction of fibrinogen with vascular cells has emerged as an alternate mechanism for recruiting leukocytes at the site of vascular injury. Although the role of fibrinogen as a risk factor for atherosclerosis has long been recognized, this pathway has been associated with complex mechanisms of intercellular adhesion, signal transduction, second-messenger generation, and modulation of gene expression in vascular cells. These studies have revealed a multifaceted and far-reaching molecular link between inflammation and hemostasis–a link that is of potential therapeutic relevance for the pathogenesis of vascular diseases.